Comparison of Oncotype DX With Modified Magee Equation Recurrence Scores in Low-Grade Invasive Carcinoma of Breast. Issue 2 (17th July 2017) - Hou, Yanjun; Zynger, Debra L.; Li, Xiaoxian; Li, Zaibo
Abstract: Objectives: Several specific histologic types of invasive carcinoma of breast, including invasive tubular carcinoma (ITC), invasive mucinous carcinoma (IMC), and classical invasive lobular carcinoma (CILC), are considered low-grade carcinomas with favorable outcomes. We aimed to investigate the utility of Oncotype DX test in these tumors by comparing its recurrence score (RS) with the modified Magee equation RS. Methods: Oncotype DX RSs were collected and modified Magee equation RSs were calculated in 163 low-grade invasive breast carcinomas, including 105 CILCs, 41 ITCs, and 17 IMCs. Results: In total, 105 (64.4%) cases had an Oncotype DX RS less than 18, 56 (34.4%) were between 18 and 30, and two (1.2%) were more than 30. Of the cases, 124 (76.1%) had a modified Magee RS less than 18, 39 (23.9%) were between 18 and 30, and no case was more than 30. The overall agreement between Oncotype DX RS and modified Magee RS risk categories was 68.7%. Two CILCs with an Oncotype DX RS more than 30 had modified Magee equation RSs of 20.3 and 20.0, respectively, and both had not shown recurrent disease. Conclusions: Performing Oncotype DX on low-grade invasive carcinomas is unlikely to provide additional useful information beyond Magee equation RS, and eliminating Oncotype DX from these cases could lead to substantial cost savings.